Quality Matrix-Based Product Innovation in Birkinpet Pet Harness Apparel - Zafriana, Lusi; Nasution, Anita Hakim; ., Prihono (UNIPA PRESS, 2024)
This study employs the Quality Function Deployment (QFD) method to develop BirkinPet pet harness apparel, focusing on customer needs and competitive advantages. A House of Quality (HoQ) matrix was constructed using responses from 96 participants, evaluating the relationship between Customer Importance and Technical Importance to identify key technical priorities for immediate implementation in BirkinPet’s production process. The primary HoQ matrix results indicate that lightweight, comfort, and safety (481.5), design for various activities (416.1), and ergonomic and comfortable design (389.9) are the most important attributes to customers. The main technical priorities include ensuring the product is safe and strong (4.99) and providing a variety of sizes and options (4.86). The novelty lies in the comprehensive and structured application of QFD, emphasizing innovation in designing products that align with current market trends and customer preferences. By integrating comfort, safety, and flexible design, BirkinPet successfully creates a high-quality product that meets customer needs, enhancing customer satisfaction and loyalty while strengthening its competitive position in the pet accessories market.